1-DOF Finger Mechanism Design for Anthropomorphic Prosthetic Hand with Similarity Criteria for Human Hand Finger Movement - Romdhoni Nur Huda; Lobes Herdiman; Taufiq Rochman (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
Development of prosthetic hands continues to be made to get prosthetic which has special characteristics, namely anthropomorphism. The anthropomorphic prosthetic design refers to the improvement and development of the design to the stage of the similarity of the prosthetic movement to human hand movements. This study carries the design of the anthropomorphic 1-DOF prosthetic finger mechanism to get prosthetic at an affordable price. The optimization criteria for the similarity of movement with the human hand are formulated with two objective functions, namely the similarity of the range of motion and the total length of the finger that is completed simultaneously. The human hand movement that is a reference is the movement of conical object grasping on a standard size conical according to the maximum hand-held diameter anthropometry of an Indonesian people.